2012
DOI: 10.1182/blood-2012-01-405555
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 3-gene model as a powerful diagnostic tool for the recognition of ALK-negative anaplastic large-cell lymphoma

Abstract: IntroductionSystemic anaplastic large-cell lymphomas (ALCLs) are a peripheral T cell-derived malignancy accounting for approximately 12% of all T-cell non-Hodgkin lymphomas (T-NHLs). 1 Originally described by Stein et al in 1985 as ALCL-expressing CD30, 2 its definition and relationship with other T-NHLs has undergone a series of revisions. 1,3,4 Based on genetic and clinical features, 2 different entities are now recognized as systemic forms, the ALK-positive (ALK ϩ ) and ALK-negative (ALK Ϫ ) ALCL. 1,5 The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 34 publications
2
84
2
Order By: Relevance
“…Interestingly however, when we excluded these "borderline" samples from the analyses, only the score of pSTAT3 was significantly different between CD30 + PTCL, NOS and ALK -ALCL (data not shown), enabling us to exclude the hypothesis of an eventual bias introduced by the inclusion of these six cases. Moreover, when applying the molecular classifiers developed by Piva et al 13 and Agnelli et al 14 to discriminate ALCL from PTCL, NOS, we found that the levels of mRNA expression of three of the four genes which could be analyzed in our dataset (TMOD1, PERP, TNFRSF8) were significantly lower in CD30 + PTCL, NOS than in ALK -ALCL, while one of the genes (BATF3) was expressed at similar levels in CD30 + PTCL, NOS and ALCL. Interestingly, the levels of expression of TMOD1, PERP and TNFRSF8 were also significantly different between CD30 -and CD30 + PTCL, NOS, being lower in the CD30 -subgroup (data not shown).…”
Section: Alkmentioning
confidence: 99%
“…Interestingly however, when we excluded these "borderline" samples from the analyses, only the score of pSTAT3 was significantly different between CD30 + PTCL, NOS and ALK -ALCL (data not shown), enabling us to exclude the hypothesis of an eventual bias introduced by the inclusion of these six cases. Moreover, when applying the molecular classifiers developed by Piva et al 13 and Agnelli et al 14 to discriminate ALCL from PTCL, NOS, we found that the levels of mRNA expression of three of the four genes which could be analyzed in our dataset (TMOD1, PERP, TNFRSF8) were significantly lower in CD30 + PTCL, NOS than in ALK -ALCL, while one of the genes (BATF3) was expressed at similar levels in CD30 + PTCL, NOS and ALCL. Interestingly, the levels of expression of TMOD1, PERP and TNFRSF8 were also significantly different between CD30 -and CD30 + PTCL, NOS, being lower in the CD30 -subgroup (data not shown).…”
Section: Alkmentioning
confidence: 99%
“…Gene-expression profiling and GSEA Gene-expression profiling (GEP) data from T-cell lymphomas were generated by our group (19). Expression data for NSCLC are publicly available (20,21).…”
Section: Methodsmentioning
confidence: 99%
“…Several attempts have been made to establish classifiers differentiating between ALK À anaplastic large cell lymphoma and peripheral T-cell lymphoma not otherwise specified, [24][25][26] but to our knowledge this has not been achieved for differential diagnosis of classical Hodgkin lymphoma and ALK À anaplastic large cell lymphoma. The aim of the present study was to find new immunohistochemical markers which can be applied in the differential diagnosis of ALK À anaplastic large cell lymphoma and classical Hodgkin lymphoma in daily routine practice.…”
Section: Discussionmentioning
confidence: 99%